Sensitive Nutrition Intervention Efforts for Adolescent Girls through Social Mapping and Local Food Product Formulation - Sari, Indah Purnama; Ningsih, Windi Indah Fajar; Arinda, Ditia Fitri (Jurnal Ilmiah Kesehatan (JIKA), 2025)
The teenage phase is a crucial period in preparing to become a woman of childbearing age who is able to prepare for the health of future generations. Therefore, nutritional status and supporting factors for growth and development in adolescence are the focus of attention in sensitive nutrition interventions. One effort to improve adolescent nutrition is through providing snacks in the form of nutritious snack bars which are formulated using local food ingredients typical of the target area. The potential of snakehead fish which has a high protein content has been used as a traditional snack such as pempek, so efforts are needed to increase the use of snakehead fish as a snack bar product. The aim of this research was to carry out social mapping and develop local food-based products as an initial project in a sensitive nutrition intervention effort to accelerate stunting reduction. Social mapping related to teenagers was carried out on 100 young women at SMA Negeri 4 Palembang and product formulation was carried out at the Nutrition Laboratory, Faculty of Public Health, Sriwijaya University. The results of the social mapping research showed that 59 subjects (59%) were at risk of CED and 30 subjects (30%) had anemia. The snack bar formulation product most liked by the trained panelists was the snakehead fish formulation with the addition of gulo puan F3, F6 and F9. The product formulation most preferred by consumer panelists is the F3 formulation.